Integrated Assessment Exists but Feels Fragmented: Pre-Service English Teachers’ Quality Perceptions in Indonesian EFL Teacher Education - I Putu Andre Suhardiana; I Dewa Gede Rat Dwiyana Putra; I Gusti Ngurah Agung Wijaya Mahardika; Ni Putu Ratni (Journal of English Language Teaching and Linguistics, 2026)
The traditional way of assessing pre-service English teachers has separated language competency from pedagogical competence, which experts refer to as an artificial duality. However, preliminary findings from an Indonesian teacher education program indicated that integrated assessment is already in place, but felt inadequate by students. The study focused on the gap between the existence and effectiveness of integrated assessment that was experienced by pre-service English teachers, particularly rubric transparency, feedback implementation, and genuineness. This study used a convergent parallel mixed-methods design with 64 pre-service English teachers of Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar. Data were acquired by a 15-item questionnaire, open-ended responses and semi-structured interviews with five selected students. Quantitative data were analyzed using descriptive statistics, and qualitative data using thematic analysis. The results showed a paradox. 81.3% of students reported experiencing integrated assessment, and 76.6% rejected the idea of fragmentation; however, 87.5% still wanted assessment to be more integrated. Three quality gaps emerged: clarity deficit of rubric (79.7% strongly acknowledged the requirement of integrated rubrics), feedback integration gap (96.9% requested integrated feedback), and authenticity problem (73.4% regarded assessments as too theoretical). Students cited five features: dual-skill rubrics, simulation-based exercises, portfolio assessment, manageable workload and reflective practice. The study finds that the problem is not the lack of integrated assessment but the quality of integration as viewed by the students.